Molar incisor hypomineralisation: Prevalence and associated risk factors among children at the Polyclinic, Kulliyyah of Dentistry, IIUM - Ardini, Yunita Dewi; Ismail, Nurul Naquiah; Mohd Azni, Nur Diyana; Harun, Nor Asilah (Elsevier, 2019)
The aim of this study was to determine the prevalence and association of molar incisor hypomineralization (MIH) with perinatal complications (PC), childhood illness (CI), and prolonged antibiotic consumption (PAC) among children attended at the Polyclinic, Kulliyyah of Dentistry, IIUM. MIH was determined based on criteria from EAPD seminar, Athens 2003. Out of 156 patients, 23 were detected having MIH within the 9 months period. Analysis of risk factors indicated significant association between MIH with CI. In conclusion, MIH was not related to gender. However, MIH was associated with CI but not with PC and PAC.